Bail support schemes for adults - Hucklesby, Anthea (Bristol : Policy Press, 2011)
This important book makes a valuable contribution to an under-researched area. It includes an evaluation of the Effective Bail Scheme (EBS) and discusses the potential for the wider development of bail support schemes and some of the questions and challenges posed by their use.
Title from publisher's bibliographic system (viewed on 07 Sep 2022).
Keywords: Bail -- England; Bail -- Wales; Bail -- England -- Yorkshire -- Case studies; Bail -- England -- Humberside -- Case studies